MobiTop: interactivity issues in a multi-mobile system - Ong, Beng Liang; Teo, Rhun Ming; Mohd Norowi, Noris; Mansor, Evi Indriasari; Dey, Prasenjit; Jamil, Izdihar (Association for Computing Machinery, 2016)
Mobile devices are increasingly becoming an important part of technology. As the demand for handling information grows, so does the need for collaboration in integrating and managing multiple forms of information. With its small screen, it is relatively uncomfortable for a group of people to perform task collaboratively. This paper presents MobiTop-a multi-mobile system that integrates mobile devices that works seamlessly together - promoting an extended screen size for the mobile devices to support collaboration. However, interactivity issues such as bezels and screen orientation are found to restrict users from performing collaborative tasks favourably. This paper discusses the interactivity issues pertaining multi-mobile systems and offers guidelines for designers.